The effect of stock market pressure on the tradeoff between corporate and shareholders' tax benefits - Ming-Chin Chen (China Journal of Accounting Research, 2015)
The Taiwanese government offers firms that invest in qualified projects in emerging high-tech industries two mutually exclusive tax incentives-a corporate 5-year tax exemption or shareholder investment tax credits. This study examines whether corporate managers take shareholder tax benefits into account in their corporate tax planning. The results show that privately held firms are more likely than listed firms to choose shareholder investment tax credits and forego corporate tax benefits. Listed firms with relatively high earnings response coefficients tend to choose a corporate 5-year tax exemption, as it can enhance reported after-tax earnings. Further, in the 5-year period following their choice of a particular tax incentive, firms choosing a corporate 5-year tax exemption exhibit significantly lower earnings persistence than those choosing shareholder investment tax credits. Taken together, these results suggest that stock market pressure has a significant effect on firms' choices between corporate and shareholder tax benefits, and that the choice of tax incentives has an effect on future earnings quality.
Keywords: 650; Corporate tax planning; Shareholder tax benefits; Stock market pressure; Financial reporting costs; Earnings persistence